Altered proteasome function in right ventricular hypertrophy. Issue 2 (24th April 2019) - Heitmeier, Tanja; Sydykov, Akylbek; Lukas, Christina; Vroom, Christina; Korfei, Martina; Petrovic, Aleksandar; Klingel, Karin; Günther, Andreas; Eickelberg, Oliver; Weissmann, Norbert; Ghofrani, Hossein Ardeschir; Seeger, Werner; et al.
Abstract: Aims: In patients with pulmonary hypertension, right ventricular hypertrophy (RVH) is a detrimental condition that ultimately results in right heart failure and death. The ubiquitin proteasome system has been identified as a major protein degradation system to regulate cardiac remodelling in the left heart. Its role in right heart hypertrophy, however, is still ambiguous. Methods and results: RVH was induced in mice by pulmonary artery banding (PAB). Both, expression and activity of the proteasome was found to be up-regulated in the hypertrophied right ventricle (RV) compared to healthy controls. Catalytic inhibition of the proteasome by the two proteasome inhibitors Bortezomib (BTZ) and ONX-0912 partially improved RVH both in preventive and therapeutic applications. Native gel analysis revealed that specifically the 26S proteasome complexes were activated in experimental RVH. Increased assembly of 26S proteasomes was accompanied by elevated expression of Rpn6, a rate-limiting subunit of 26S proteasome assembly, in hypertrophied cardiomyocytes of the right heart. Intriguingly, patients with RVH also showed increased expression of Rpn6 in hypertrophied cardiomyocytes of the RV as identified by immunohistochemical staining. Conclusion: Our data demonstrate that alterations in expression and activity of proteasomal subunits play a critical role in the development of RVH. Moreover, this study provides an improved understanding on the selective activation of the 26S proteasome in RVH that might be driven by the rate-limiting subunit Rpn6. In RVH, Rpn6 therefore represents a more specific target to interfere with proteasome function than the commonly used catalytic proteasome inhibitors.